DOMINANCE OF EUROPEAN CULTURE IN TODAY’S SOCIETY - Huang, Gary (PEOPLE: International Journal of Social Sciences, 2019)
Throughout modern history, we can see that Western culture has influenced the life of people all of the world and the way we think. My research is focused on European colonialism and its impact on modern society. My reference materials in the research process include scholarly articles and current news articles. The findings of my research are that almost all of the issues and trends today are somewhat related to colonialism. Even though colonialism has long ended, its legacies remain in today’s society and has shaped the way of our thinking today, as it has led to dominance of European culture in the world. This paper examines colonialism’s impact in many different areas, including politics, economics, religion, language, clothing, and cuisine, using examples from different parts of the world, including Africa, Asia and South America. Based on the research, I have found the profound influence of European colonialism on today’s society and people’s way of thinking.